Effect of radiation damage on the migration behaviour of Europium implanted into both single crystalline 6H-SiC and polycrystalline SiC - Hlatshwayo, Thulani Thokozani (University of Pretoria, 2022)
Thesis (PhD (Physics))--University of Pretoria, 2021.